CONTRACEPTIVE ATTITUDE AND BEHAVIOUR AMONG UNIVERSITY MEN: A STUDY FROM PUNJAB, PAKISTAN - Nasir, Jamal Abdul; Tahir, M. H.; Zaidi, Arif Ahmed (Journal of Ayub Medical College Abbottabad, 2010)
Background: The men’s attitudes towards family planning and on the use of family planning method may affect not only their wives intention to use contraception but also the choice of a particular family planning method. This focus of this study is to assess the educated men’s role, belief, practice and their participation in family planning. Methods: A cross-sectional data on 150 university male employees was taken. The logistic regression in connection with stepwise procedures is used to find the most significant variables that influence the men’s current use of contraception status. Results: About 42 percent of the married male employees were users of family planning methods. Among family planning methods, condom was the most used method (about 71%) followed by traditional methods (14%). The mean age at first marriage of the respondents was 23 years and for the spouses it was 19 years. Conclusion: The knowledge of men in family planning methods is quite universal and general; but the attitude on the use of contraceptives and the family planning method is much different between the employees who had the awareness of contraception and those who had no awareness. Keywords: Age at marriage, contraception, family planning, logistic regression, men’s attitude, stepwise procedure